ISOLASI SENYAWA FENOLIK PADA FRAKSI METANOL-AIR DARI UMBI TUMBUHAN SARANG SEMUT (Myrmecodia tuberose Jack) - Daniel - (JURNAL KIMIA MULAWARMAN, 2010)
The Isolation of phenolic compound in methanol-water fraction from Myrmecodia tuberosa Jack that come from Bulungan have been done. The air-dried powdered from corm of ant plant (Myrmecodia tuberosa Jack) (250 gram) were extracted by methanol at room temperature      (27 oC) and fractioned with n-hexane then ethyl acetate. Partition of phenolic compounds in Methanol-Water fraction was chromatographed on silica gel column (35–70 mesh) that eluted with Isocratic method and gave 10 fractions as a result, that fractions were A, B, C, D, E, F, G, H, I dan J fraction. C; E; G and H (alliance fraction) gave the best spot partitioned and the spot was not fluorescence. Purification of alliance fraction gave yellow-brown crystal with retention factor 0.52 that eluted with methanol : ethyl acetat (8:2) whereas the retention factor in methanol 0.82 and ethyl acetate 0,33. Infrared spectrum of alliance fraction shown absorption at value : 3351.83; 2945.33; 2833.04; 1741.00; 1451.60; 1215.67; 885.74 and 776.74 cm-1 with melting point 224 - 228oC. UV and Visible spectrum of alliance fraction shown wavelength at value 263 and 334 nm. Phenolic compounds in Methanol-Water fraction from the corm of ant plant (Myrmecodia tuberosa Jack) was predictioned as phenolic compound of flavonoid group.Keywords : Ant Plant (Myrmecodia tuberosa Jack), Phenolic, Isocratic , Flavonoid, Isolation,